Assessment Tingkat Kerentanan Bangunan Bertingkat di Kampus Universitas Negeri Padang Menggunakan Gelombang Rayleigh - Rusnardi Rahmat Putra; Dezy Saputra (Fakultas Teknik, 2022)
In 2009 the city of Padang experienced an earthquake with a magnitude of 7.9 SR which resulted in damage to many high-rise buildings in the city of Padang, including multi-storey buildings on the UNP campus. Over time the multi-storey building will experience a decrease in quality so it is necessary to check the quality of the building itself. In this study, the author chose one of the multi-storey buildings on the UNP campus to be the object of research, namely the Faculty of Economics building. The purpose of this study was to determine the level of vulnerability of the Faculty of Economics building by checking without damaging it using a microtremor device. The research method was carried out by recording the frequency of the soil and buildings under study using a microtremor device. The primary data of this research is in the form of seismic wave data which will be processed using Matlab and Bido 2.02 software to obtain the natural frequency value of the building itself. Based on the data processing that has been done, the resonance index of the Faculty of Economics UNP building ranges from 584.81%-1054.23% so it is in the low category. The vulnerability index of the UNP Faculty of Economics building ranges from 7.07–29.21 with the highest value on the 1st floor so that the 1st floor is the most vulnerable floor.